The CGIAR’s Challenge Program Experiences: A Critical Analysis - Woolley, Jonathan N.; Ribaut, J.M.; Bouis, Howarth E.; Adekunle, A.A. (2009)
This document has been prepared by staff of the four Challenge Programs (CPs) established by the CGIAR in 2002-2004 as a contribution to the first meeting of the Consortium Planning Team (CPT) with the Alliance Executive and Deputy Executive (17-20 February 2009).